2015
DOI: 10.1063/1.4922321
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of crystals that are mixed composites of all three polymorphs in the Gaussian core model

Abstract: Articles you may be interested inCross-nucleation between clathrate hydrate polymorphs: Assessing the role of stability, growth rate, and structure matching J. Chem. Phys. 140, 084506 (2014) We present results of computer simulations of homogeneous crystal nucleation in the Gaussian core model. In our simulations, we study the competition between the body-centered-cubic (bcc), face-centered-cubic (fcc), and hexagonal-close-packed crystal phases. We find that the crystal nuclei that form from the metastable flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…A natural extension of the ideas presented in the previous section is their application to polymorph selection, which has attracted a lot of investigations [1,2,44,103,111,[141][142][143][144][145][146].…”
Section: Role Of Precursors In Polymorph Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural extension of the ideas presented in the previous section is their application to polymorph selection, which has attracted a lot of investigations [1,2,44,103,111,[141][142][143][144][145][146].…”
Section: Role Of Precursors In Polymorph Selectionmentioning
confidence: 99%
“…Ref. [145] then found that the nuclei have a mixed nature, not consisting of a single polymorph, and that the kinetic pathway selected during nucleation persists even when the nucleus is many times above its critical size.…”
Section: Role Of Precursors In Polymorph Selectionmentioning
confidence: 99%
“…Polymorph selection plays a fundamental role in many applications, and has been the subject of many investigations [31,52,64,84,85].…”
Section: Polymorph Selectionmentioning
confidence: 99%
“…This state forms via the conventional nucleation then growth kinetics of a first-order transition, see Mithen et al 30 for further details.…”
mentioning
confidence: 99%
“…It did not occur in direct simulations. We attempted Forward Flux Sampling (FFS) 30,34 simulations of fcc nucleation from our bcc states, but they were unsuccessful. So although we expect that the bcc phase will ultimately transform into the fcc phase, the bcc phase is clearly stable for long periods.…”
mentioning
confidence: 99%